2022
DOI: 10.3390/ani12202805
|View full text |Cite
|
Sign up to set email alerts
|

Are Marine Heatwaves Responsible for Mortalities of Farmed Mytilus galloprovincialis? A Pathophysiological Analysis of Marteilia Infected Mussels from Thermaikos Gulf, Greece

Abstract: Marine heatwaves (excessive seawater temperature increases) pose high risk to bivalves’ health and farming. The seawater temperature increase is responsible for various pathogen population expansions causing intense stress to marine organisms. Since the majority of knowledge so far derives from laboratory experiments, it is crucial to investigate stress responses in field conditions in order to understand the mechanisms leading to bivalves’ mortality events after exposure to temperature extremes. Thus, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…Critical declines, even extinction, from highly important habitats such as Thermaikos Gulf (North Greece) have been monitored during the period of extensive temperature raise during the autumn and winter of 2022. Moreover, high mortality of P. nobilis juveniles was also detected in both Chalkididi and Vistonikos Gulf (North Aegean Sea) during extensive periods of high temperature [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Critical declines, even extinction, from highly important habitats such as Thermaikos Gulf (North Greece) have been monitored during the period of extensive temperature raise during the autumn and winter of 2022. Moreover, high mortality of P. nobilis juveniles was also detected in both Chalkididi and Vistonikos Gulf (North Aegean Sea) during extensive periods of high temperature [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that infections with protozoan parasites induce immune responses in marine bivalves regardless of the effects of the thermal stress [ 17 ]. Specifically, mussels infected with the protozoan parasite Marteilia refringens exhibited increased inflammation, as well as apoptotic, responses [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bivalve mollusc aquaculture as well as natural bivalve populations, appear to be especially vulnerable to the threats arising from the climate change. Several factors are accountable for mass mortalities of bivalves (Fleury and Huvet, 2012; Soon and Zheng, 2020; Lattos et al ., 2022), however, incidents of most mass mortalities are stimulated by the synergistic effects of more than one factor (Callaway et al ., 2013). Harmful impacts might immerge from the increasing sea temperature, decreasing pH and elevated frequency of extreme climatic events, while possible synergies with other kinds of stressors, including diseases and harmful algal blooms could intensify the threat to marine bivalve molluscs (Rodrigues et al ., 2015) leading to repeated mortality outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Warm temperate marine invertebrates' thermal tolerance thresholds may be influenced by internal (systemic) hypoxia that occurs at both low-and high-temperature extremes, in fully oxygenated waters [Oxygen-and Capacity-Limited Thermal Tolerance (OCLTT)] (Pörtner 2010). Oxygen-and Capacity-Limited Thermal Tolerance can, therefore, explain the, reported in numerous countries, summer mass mortalities of bivalves (Cotter et al 2010, Fleury & Huvet 2012, Rodrigues et al 2015, Theodorou et al 2019, Lattos et al 2022. Pathogens and biofouling may increase the existing stress by narrowing the mussels' thermal window, therefore, enhancing the mortality rates (Samain & McCombie 2008).…”
Section: Introductionmentioning
confidence: 99%